Ayurvedic Management of Acute Dissociative Reactions to Stressful Life Events - A Case Study (International Journal of Ayurveda and Pharma Research, 2023)
Mental diseases known as dissociative disorders are characterised by a sense of discontinuity and separation from one's thoughts, memories, environment, activities, and identity. People with dissociative disorders unintentionally and unhealthily flee reality, which makes it difficult for them to carry on with daily activities. Dissociative identity disorder (DID, sometimes known as multiple personality disorder), fugue, "psychogenic" or "functional" amnesia, and depersonalization disorder are examples of dissociative disorders. Other specified dissociative disorder is subcategory of dissociative disorders that describes presentations in which symptoms are typical of a dissociative disorder but do not fully match the diagnostic criteria for any of the illnesses in the diagnostic class of dissociative disorders. In Ayurveda this condition can be considered as Unmada. 34 year female patient hailing from Malappuram, Kerala, brought to Manasanthi OPD of VPSV Ayurveda College, Kottakka,l by husband and relatives complains of lack of desire to live, wants to end her life, loss of sleep, difficulty to walk and doing daily activities since 3 days. She was very much concerned about the behavioural issues and wellbeing of her elder son since 12 years. According to the informant, the patient was having increased tension, repeated talking about her elder son, making loud noises and suicidal thoughts. Also, she had an attempt to suicide. She was treated on an IP level with a combination of Ayurvedic internal medications and Panchakarma procedures. The treatment protocol includes Snehapana, Virecana, Nasya, Shirodhara, and Dhoopana. Satvavajaya methods including Yoga also administered. There were considerable relief from symptoms and HAM D score was reduced from 21 to 6.